Insight into the interaction between arabinoxylan and imidazolium acetate-based ionic liquids. (1st March 2020) - Hu, Lifang; Peng, Hong; Zhang, Yu; Xia, Qi; He, Hongwei; Ruan, Roger; Liu, Yuhuan; Liu, Aihong
Highlights: The temperature and cation affected the solubilities of arabinoxylan in the ILs. The structure of cation greatly affected the hydrogen bond accepting ability of Ac − . Both the cation and Ac − played an important role in the solvation of arabinoxylan. But Ac − performed the major factor in the solubilization of arabinoxylan. The ratio of arabinoxylan to ILs affected the formation of hydrogen bond. Abstract: Herein, six ionic liquids (ILs) with different cations and the same anion of acetate (Ac − ) were used to dissolve arabinoxylan. These ILs included N-methylimidazolium acetate (HmimAc), 1-ethyl-3-methylimidazolium acetate (EmimAc), 1-hydroxyethyl-3-methylimidazolium acetate (HOemimAc), 1-propyl-3-methylimidazolium acetate (PrmimAc), 1-allyl-3-methylimidazolium acetate (AmimAc), and 1-butyl-3-methylimidazolium acetate (BmimAc). The solubilities of arabinoxylan in these ILs were determined, and the dissolution mechanism was explained using 1 H and 13 C NMR techniques. The solubilities of arabinoxylan in the ILs were in the order: BmimAc > EmimAc > AmimAc > PrmimAc > HOemimAc > HmimAc. Both the cation and Ac − played an important role in the solubilization of arabinoxylan, but Ac − performed the major factor. The structure of cation greatly affected the hydrogen bond accepting ability of Ac − . Increasing the mass ratio of arabinoxylan to ILs resulted in stronger hydrogen bond between arabinoxylan and the ILs. Both the solubility and the strength of hydrogen-bonding interaction between arabinoxylan and the ILs decreased in the recycled ILs because of the impurities remained.